Degenerate sequence recognition by the monomeric restriction enzyme: single mutation converts BcnI into a strand-specific nicking endonuclease - Kostiuk, Georgij (Oxford University Press, 2011)
Unlike orthodox Type II restriction endonucleases that are homodimers and interact with the palindromic 4–8-bp DNA sequences, BcnI is a monomer which has a single active site but cuts both DNA strands within the 5′-CC↓CGG-3′/3′-GGG↓CC-5′ target site (‘↓’ designates the cleavage position). Therefore, after cutting the first strand, the BcnI monomer must re-bind to the target site in the opposite orientation; but in this case, it runs into a different central base because of the broken symmetry of the recognition site. Crystal-structure analysis shows that to accept both the C:G and G:C base pairs at the center of its target site, BcnI employs two symmetrically positioned histidines H77 and H219 that presumably change their protonation state depending on the binding mode. We show here that a single mutation of BcnI H77 or H219 residues restricts the cleavage activity of the enzyme to either the 5′-CCCGG-3′ or the 5′-CCGGG-3′ strand, thereby converting BcnI into a strand-specific nicking endonuclease. This is a novel approach for engineering of monomeric restriction enzymes into strand-specific nucleases.